2021
DOI: 10.1094/mpmi-06-21-0142-r
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Sucrose and Phenylpropanoid Metabolism Affected by BABA-Primed Defense in Postharvest Grapes and the Associated Transcriptional Mechanism

Abstract: Defense elicitors can induce fruit disease resistance to control postharvest decay but may incur quality impairment. Our present work aimed to investigate the resistance against Botrytis cinerea induced by the elicitor β-aminobutyric acid (BABA) and to elucidate the specific transcriptional mechanism implicated in defense-related metabolic regulations. The functional dissection results demonstrated that, after inoculation with the fungal necrotroph B. cinerea, a suite of critical genes encoding enzymes related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…A direct connection between D-tagatose and D-glucose metabolism has been reported in the oomycete P. infestans [ 27 ]. D-glucose may also be redirected to the phenylpropanoid pathway for the synthesis of phytoalexins, resulting in enhanced resistance [ 58 ]. Structural similarity of D-tagatose with common sugars is probably a crucial factor contributing to its effect.…”
Section: Discussionmentioning
confidence: 99%
“…A direct connection between D-tagatose and D-glucose metabolism has been reported in the oomycete P. infestans [ 27 ]. D-glucose may also be redirected to the phenylpropanoid pathway for the synthesis of phytoalexins, resulting in enhanced resistance [ 58 ]. Structural similarity of D-tagatose with common sugars is probably a crucial factor contributing to its effect.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq and comparative transcriptomic analysis revealed that treatment of grapes with 100 mM BABA relatively upregulated genes associated with phenylpropanoid biosynthesis compared with grapes subjected to 10 mM BABA treatment. These results suggested that the BABA-primed defense determines alterations in sucrose and phenylpropanoid metabolism in postharvest grapes (Li et al, 2021a). Interestingly, the grape MYB-type transcription factor VvMYB44 directly activates the expression of sucrose and phenylpropanoid metabolism-related genes, and might participate in BABA-induced priming (Li et al, 2021a).…”
Section: Physiological Transcriptional and Metabolic Changes During P...mentioning
confidence: 95%
“…These results suggested that the BABA-primed defense determines alterations in sucrose and phenylpropanoid metabolism in postharvest grapes (Li et al, 2021a). Interestingly, the grape MYB-type transcription factor VvMYB44 directly activates the expression of sucrose and phenylpropanoid metabolism-related genes, and might participate in BABA-induced priming (Li et al, 2021a).…”
Section: Physiological Transcriptional and Metabolic Changes During P...mentioning
confidence: 95%
See 1 more Smart Citation
“…The Mapman analysis confirmed the GO enrichment data, showing that major metabolic pathways were similarly induced following infection in both BABA-treated and untreated plants, although some bins within each pathway were differently expressed between treatments. BABA has been shown to induce expression of genes involved in phenylpropanoid and salicylic acid (SA) biosynthesis associated with reduced decay incidence when applied locally ( Li et al., 2021 ). However, except for the reduced expression of genes involved in photosynthesis the induced susceptibility observed in our study does not seem to be explained by induction or repression of major metabolic pathways, but rather by differential expression of individual genes that might induce susceptibility.…”
Section: Discussionmentioning
confidence: 99%